Investing in toll highway: private or public financing with scenario-based solution - Hassan, Mazlan; Ibrahim, Abdul Razak (Universiti Putra Malaysia Press, 2013)
Whilst governments worldwide juggle competing priorities within the context of limited budgets, Malaysia has acted to seek more effective ways of building highways. In Malaysia, private involvement is allowed for the construction of highways in order to stimulate economic activity that is rarely matched elsewhere. This private finance involvement is able to reduce the public sector workforce and increase employment opportunities. However, most of the private or public/private toll highway project partnerships in the 80s and 90s have yet to yield any hard evidence of being successfully profitable, since few of the typically 30- to 50-year concession agreements have yet to mature. This paper provides a financing appraisal and scenario-based solution to aid private or public decision-making to finance highway projects.